2016
DOI: 10.1128/aac.00270-16
|View full text |Cite
|
Sign up to set email alerts
|

In VitroActivity of Polymyxin B in Combination with Various Antibiotics against Extensively Drug-Resistant Enterobacter cloacae with Decreased Susceptibility to Polymyxin B

Abstract: Against extensively drug-resistant (XDR) Enterobacter cloacae, combination antibiotic therapy may be the only option. We investigated the activity of various antibiotics in combination with polymyxin B using time-kill studies (TKS). TKS were conducted with four nonclonal XDR E. cloacae isolates with 5 log 10 CFU/ml bacteria against maximum, clinically achievable concentrations of polymyxin B alone and in two-drug combinations with 10 different antibiotics. A hollow-fiber infection model (HFIM) simulating clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Synergy testing is typically not performed with the exception of research settings. The use of hollow-fiber-infection-model (HFIM) for synergy testing has been reported for testing antibiotic combinations for synergy (Lim et al, 2015 ; Cai et al, 2016b ). The HFIM is used to simulate the pharmacokinetics and pharmacodynamics of the tested drugs singly and in combination with time-kill studies.…”
Section: Laboratory Testing and Treatment In The Era Of Carbapenem Rementioning
confidence: 99%
“…Synergy testing is typically not performed with the exception of research settings. The use of hollow-fiber-infection-model (HFIM) for synergy testing has been reported for testing antibiotic combinations for synergy (Lim et al, 2015 ; Cai et al, 2016b ). The HFIM is used to simulate the pharmacokinetics and pharmacodynamics of the tested drugs singly and in combination with time-kill studies.…”
Section: Laboratory Testing and Treatment In The Era Of Carbapenem Rementioning
confidence: 99%
“…However, due to the lack of new Ab development, PMBs continued to be used in clinical practice, even with the pharmacokinetic/pharmacodynamic limitations and increased risk of severe renal insufficiency. It was found that PMBs might promote membrane transport of other Abs, thereby enhancing bactericidal or bacteriostatic activities (2,3). The broad-spectrum antimicrobial agent, tigecycline (TGC), was also active against most Gram-negative isolates in vitro, including ESBL producers.…”
Section: Introductionmentioning
confidence: 99%
“…If the actual number of colonies in the undiluted drop in a series is lower than the number of colonies in subsequent dilutions, this suggests antibiotic carryover effect. Different options have been described for preventing this effect, including spreading a single aliquot over an entire plate 38 or spinning down the sample, removing the supernatant, and re-suspending in sterile saline prior to plating 39 . At each time point in the time-kill method, it is also critical for the investigator to efficiently but accurately remove an aliquot from each culture tube and perform serial dilutions.…”
Section: Discussionmentioning
confidence: 99%